Salvage Operation of Head and Neck Reconstruction Using a Pedicled Latissimus Dorsi Myocutaneous Flap with Distally Positioned Skin Paddle - Tsubasa Kojima, MD; Hisashi Motomura, MD, PhD; Ayaka Nochi Deguchi, MD; Shusaku Maeda, MD; Songsu Kang, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. There are many situations in head and neck reconstruction where a pedicled flap must be chosen over free flaps. In such situations, one of our options is a pedicled latissimus dorsi (LD) myocutaneous flap with distally positioned skin paddle with a more distal skin flap design. Methods:. We performed 22 reconstruction cases using a distally positioned pedicled LD myocutaneous flap. When designing the skin paddle more distally than usual, it is important to include the lateral cutaneous branch of the 10th posterior intercostal artery. By splitting the skin paddle sections, the LD flap is flexible for use in complex head and neck defects. It can also be used for mandibular reconstruction by harvesting the flap with costal bone. Results:. In all cases, the skin flaps survived, with a salvage rate of 100%. Conclusions:. Because elevation of this flap is relatively easy, safe, and quick, this flap selection is considered practical in salvage cases after flap necrosis, and in cases after multiple procedures.